PENDAPATAN DAERAH DAN SIKLUS POLITIK KABUPATEN/KOTA DI INDONESIA - Rahman, Rahman (Jurnal Ekobistek, 2018)
Political budget cycle (PBC) is a situation in which government budget pattern is affected by political cycle. PBC is usually used to increase incumbent?s re-election probability through changing budget deficit, total spending, spending allocation or revenue during or prior to an election year. The existence of PBC has been found in both established democracies and newly democratic countries. For Indonesia, PBC from government expenditure at the district level has been identified by Sjahrir et al (2013). In this paper, we attempt to investigate whether district government revenues also follow local political cycle. Using a panel data of 491 districts in Indonesia from 2005 to 2013, we found that local own source revenue classified in ?miscellaneous revenues? is decreasing during the district election year.